2020
DOI: 10.3390/w12072011
|View full text |Cite
|
Sign up to set email alerts
|

Hydropower Potential in the Alps under Climate Change Scenarios. The Chavonne Plant, Val D’Aosta

Abstract: Present and prospective climate change will likely affect the hydrological cycle in sensitive areas, such as the Alps, thus impacting water-based activities. A most representative example is hydropower production, i.e., exploitation of water to produce energy. In the Italian Alps hydropower is strictly dependent upon water from snow and ice melt, and both are decreasing in response to global warming. Here, we study the effects of potential climate change scenarios at 2100 upon hydropower production from the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Research has shown that this impact depends on the region and hydrological characteristics [89,90]. The most vulnerable areas are mountain areas, which are dependent on glacial water [91], as well as desert areas (e.g., the Middle East) [92] or the Mediterranean climate [93]. Running water is also more at risk than standing water due to its inability to store water [94].…”
Section: Preliminary Analysis Of the Relationship Between The Level Omentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that this impact depends on the region and hydrological characteristics [89,90]. The most vulnerable areas are mountain areas, which are dependent on glacial water [91], as well as desert areas (e.g., the Middle East) [92] or the Mediterranean climate [93]. Running water is also more at risk than standing water due to its inability to store water [94].…”
Section: Preliminary Analysis Of the Relationship Between The Level Omentioning
confidence: 99%
“…There are countries that, despite high water resources, are no longer able to build new hydropower plants due to their unprofitability [112]. For example, Alpine countries have the technology and resources to implement new projects, but lack water resources available that are profitable for hydropower development [91]. This is most often the case in Europe and North America, where 75% and 69% of the hydropower potential is used, respectively [103].…”
Section: Region Predicted Impact Of Climate Change On Hydropower Refementioning
confidence: 99%
“…The reason we assessed these losses is in the character of the Sava River, which is a typical sub-Alpine river [16]. Flood events are more frequent in the Spring, when the snow melts in the Alps, and in Autumn when heavy rainfalls occur.…”
Section: Introductionmentioning
confidence: 99%
“…provided a synthesis and comparison of methodologies and results obtained in several studies devoted to the impact of climate change on hydropower on Swiss and Italian Alps [12]. Duratorre et al (2020) studied the effects of potential climate change scenarios at 2100 upon hydropower production from the Chavonne plant, in Valle d'Aosta region of Italy, using Poli-Hydro, a state-of-the-art hydrological model to mimic the hydrological budget of the area, including ice and snow melt share [13]. Patro et al (2018) assessed the impacts of nine climate-change scenarios on the hydrological regime and on hydropower production of forty-two glacierized basins across the Italian Alps, for the period 2016-2065.…”
Section: Introductionmentioning
confidence: 99%